Mechanism of photocatalytic activity improvement of AgNPs/TiO2 by oxygen plasma irradiation. Issue 38 (20th September 2016) - Fang, Yingcui; Zhang, Bing; Hong, Liu; Zhang, Kang; Li, Gongpu; Jiang, Jun; Yan, Rong; Chen, Junling
Abstract : The LSPR damping of AgNPs on TiO2 by Ag2 O formed during oxygen plasma irradiation improves the photocatalytic activity. Abstract : Plasmonic metal Ag nanoparticles (AgNPs) on TiO2 thin films (AgNPs/TiO2 ) are a kind of excellent photocatalyst of high efficiency under visible light, and thus draw great interest nowadays. Further improvement of their photocatalytic activity (PA) is difficult but is of high importance for their applications. In this paper, oxygen plasma was taken to partially oxidize AgNPs deposited on the surface of TiO2 to form a structure with the configuration of a p-type semiconductor/plasmonic metal/n-type semiconductor (Ag2 O/AgNPs/TiO2 ). The localized surface plasmon resonance (LSPR) of the AgNPs was strongly damped after oxygen plasma irradiation (OPI) but the photocatalytic activity was improved. The mechanisms of the photocatalytic activity improvement under UV and visible light were explored based on charge kinetics.